Risk factors and Parkinson's disease presentations in primary care in a diverse UK population. Issue 9 (12th August 2022) - Simonet, Cristina; Bestwick, Jonathan; Jitlal, Mark; Waters, Sheena; Ben-Joseph, Aaron; Mar-Shall, Charles R; Dobson, Ruth; Jacobs, Benjamin M; Schrag, Anette; Noyce, Alastair J
Abstract : Background: Early features of Parkinson's disease (PD) have been described through population-based studies, which over-represent white, affluent groups and may not be generalisable. Methods: A nested case-control study was conducted in East London using primary care health records. A matched analysis with multivariable logistic regression was used to determine associations between risk factors and pre-diagnostic presentations with subsequent PD. Results: 1, 055 patients with PD and 10, 550 controls were included. The strongest associations were found for tremor (OR, 145.96; 95% CI, 90.55-235.28) and memory complaints (OR, 8.6; 95% CI, 5.91-12.49) <2 years before PD diagnosis which persisted up to 10 and 5 years prior to PD diagnosis respectively. Hyperten- sion (OR, 1.36; 95% CI, 1.19-1.55) and type 2 diabetes (OR, 1.39; 95% CI, 1.19-1.62) were associated with subsequent PD. Novel associations were found for epilepsy (OR, 2.5; 95% CI, 1.63-3.83) and hearing loss (OR, 1.66; 95% CI, 1.06-2.58) which were then replicated using data from UK Biobank. No association with future PD was found for ethnicity or deprivation index. Conclusions: Here we present evidence for a range of comorbidities and symptoms encountered in primary care prior to PD diagnosis in a diverse population. Convincing novel associations were observed for epilepsy and hearing loss with subsequent PD. The prominence of memory symptoms hints at an excess of early cognitive dysfunction in this population or limited ascertainment in traditionally under- represented groups.